Dimensionality and Predictive validity of the Classroom Learning Activities Checklist in Prekindergarten - Reynolds, Arthur J. (Educ Assess Eval Account, 2019)
The Classroom Learning Activities Checklist (CLAC) is a brief classroom observation measure that assesses task-oriented and self-regulated learning in early childhood environments. We assessed the tool’s dimensionality and validity in predicting prekindergarten (PreK) learning gains. The study sample is from the Midwest Child-Parent Center (MCPC) program, an evidence-based PreK–3rd grade school reform model providing comprehensive educational and family support services. Data from 1358 enrolled students in 72 observed classrooms indicated that a 2-factor model—instructional responsiveness and student engagement—explained 50% of the variance in item scores. Evidence for construct validity was strong. Linear and probit regression analyses indicated that CLAC scores independently predicted learning gains in literacy (ES = .34 SD) and math (ES = .30 SD) on the Teaching Strategies Gold Assessment System, a standardized performance assessment. Findings support the validity of the CLAC in assessing the classroom learning environment. Implications for program monitoring, evaluation, and professional development are discussed.